Walking in Consumers' Shoes : Reshaping the Pharmacy Student Placement Curriculum via Mystery Shopping with Feedback : Final Report. - Schneider, Carl; Moles, Rebekah (Office for Learning and Teaching, 2016)
Experiential placements in community pharmacy are an essential requirement of pharmacy curricula. These clinical placements aim to integrate theoretical learning in a community pharmacy environment to develop clinical competence. However, these placements traditionally entail passive observation by shadowing the community pharmacist. Research has highlighted that often pharmacy students do not feel adequately prepared for practice on graduation. Some pharmacy students are unhappy with current community pharmacy placements stating they are repetitive and lack direction. In this project, students will act as mystery shoppers as part of the clinical placement curriculum. This structured work-integrated learning activity will enable students to reflect on the patient experience and pharmacy staff practice, and, develop skills in appropriate medicine supply and provision of feedback to pharmacy staff. We propose that this activity will address current placement shortcomings. We will compare student academic performance, clinical competence, and engagement in research between students undertaking this supplemental placement with students undertaking the traditional experiential placement curriculum alone.